Sensitivity, Affectivity, and Reflection in the Classroom: A Lack in Teacher's Work - Madríz Rojas, Marco (2012)
Sensitivity should be an intrinsic quality of teaching to achieve better interaction with students, recognizing them as persons. However, in our national education system, discourses aiming to approach students prevail, but they are rarely put into practice, leaving aside the emotional closeness and creating barriers that separate educators from their students to a great extent. In this regard, the promotion of comprehensive educational strategies is necessary from the teacher’s reflection to return a voice to the students and recognize their individual identity, so that education becomes a tool to achieve the personal development of learners.